USAHA SEKOLAH DALAM MENGATASI SISWA YANG MEMBOLOS (Studi Kasus pada Siswa Kelas X di SMA Muhammadiyah 4 Kartasura Sukoharjo) - Sundari, S.; Prasetyo, Agus (HISTORIKA, 2018)
This study aims to describe the school's efforts in dealing with students who are truant in SMA Muhammadiyah 4 Kartasura Sukoharjo. This type of research is a qualitative single case study with strategy. Data source this study is the informant, places, events, and documents. Using data collection techniques interviews, observation, and documentation. To test the validity of the data in this study using triangulation techniques and sources. The data have been compiled, analyzed the use of interactive models, Miles and Huberman. . The results of this research proves that the cause of the students truant because of two factors, namely the internal and external factors. Internal factors include the motivation and ability of students. External factors include family circumstances, the influence of friends, school rules and the teaching and learning activities. Action handling school students truant by involving caregivers, community, and all the components of the school.